Response Letter to Koivisto et al. 'Evaluating the Theoretical Background of STOFFENMANAGER® and the Advanced REACH Tool'. Issue 4 (19th February 2022) - Fransman, Wouter; Arnone, Mario; Borghi, Francesca; Cattaneo, Andrea; Cavallo, Domenico M; Cherrie, John W; Franken, Remy; Galea, Karen S; van der Haar, Rudolf; Heussen, Gerardus A H; Jensen, Keld A; Koponen, Milja; et al.
Abstract: In this article, we have responded to the key statements in the article by Koivisto et al . (2022) that were incorrect and considered to be a biased critique on a subset of the exposure models used in Europe (i.e. ART and Stoffenmanager®) used for regulatory exposure assessment. We welcome scientific discussions on exposure modelling (as was done during the ISES Europe workshop) and criticism based on scientific evidence to contribute to the advancement of occupational exposure estimation tools. The tiered approach to risk assessment allows various exposure assessment models from screening tools (control/hazard banding) through to higher-tiered approaches. There is a place for every type of model, but we do need to recognize the cost and data requirements of highly bespoke assessments. That is why model developers have taken pragmatic approaches to develop tools for exposure assessments based on imperfect data. We encourage Koivisto et al . to focus on further scientifically robust work to develop mass-balance models and by independent external validations studies, compare these models with alternative model tools such as ART and Stoffenmanager®.